A comparison of the predictive validity of the combination of the neutrophil-to-lymphocyte ratio and platelet-to-lymphocyte ratio and other risk scoring systems for intravenous immunoglobulin (ivig)-resistance in Kawasaki disease. - Seiichiro Takeshita; Takashi Kanai; Yoichi Kawamura; Yusuke Yoshida; Shigeaki Nonoyama (PLoS ONE)
Background We recently reported that the combination of the neutrophil-to-lymphocyte ratio (NLR) and the platelet-to-lymphocyte ratio (PLR) is a novel and useful predictor of intravenous immunoglobulin (IVIG)-resistance in Kawasaki disease (KD). In the present study, to evaluate the effectiveness of the new risk score, we compared its predictive validity to that of previously reported risk scores. Materials and methods The laboratory records of 437 patients with KD before IVIG therapy were retrospectively analyzed, and the IVIG-responsive (n = 344) and IVIG-resistant (n = 93) patients were compared. The validity of the new score (the combination of NLR≥3.83 and PLR≥150) for predicting IVIG resistance in KD was compared to that of the Kobayashi, Egami and Sano risk scores. Results The new score and the Kobayashi score displayed high sensitivity (0.72 and 0.70 respectively) and specificity (0.67 and 0.68 respectively), while the Egami and Sano scores showed high specificity (0.71 and 0.81 respectively) but relatively low sensitivity (0.56 and 0.45 respectively). The odds ratios (ORs) for the new score, the Kobayashi score, the Egami score and the Sano score were 5.34 (95% confidence interval [CI] 3.22-8.85), 4.87 (95% CI 2.96-8.01), 3.14 (95% CI 1.96-5.03) and 3.53 (95% CI 2.17-5.77) respectively. Conclusions The predictive validity of the combination of NLR≥3.83 and PLR≥150, which is a simple and convenient indicator, was equal to or higher than that of the other risk scores. This suggests that the new score could be a widely available marker for predicting IVIG resistance in KD.